Transport of the uremic toxin symmetric dimethylarginine (SDMA) by renal transport proteins - Lorenz A. Scherpinski; Martin F. Fromm; Renke Maas; Jörg König (Amino Acids, 2025)
Abstract The L-arginine derivative and uremic toxin symmetric dimethylarginine (SDMA) is an independent risk marker for total mortality and cardiovascular events. Interferences with L-arginine- or L-homoarginine-related signaling, metabolism, or transport have been proposed as underlying mechanisms. SDMA is endogenously formed and predominantly eliminated via the kidney. Whereas for L-arginine and other L-arginine derivatives such as L-homoarginine and asymmetric dimethylarginine (ADMA) key transport proteins involved in the cellular uptake and release have been characterized, comparable data for the transport of SDMA are lacking. Using HEK cell lines overexpressing the transport proteins OCT2, OATP4C1, MATE1, OAT4, and OAT10, which are all expressed in renal proximal tubule cells, and the ubiquitously-expressed transport protein CAT1 we performed uptake experiments demonstrating that SDMA is a substrate for CAT1, OATP4C1, OCT2, and MATE1 in physiological concentrations, but not of OAT4 and OAT10. Km values for OATP4C1-, CAT1-, and MATE1-mediated SDMA uptake were 70 µM, 246 µM, and 1 973 µM, respectively. For OCT2-mediated uptake, no saturation could be reached, precluding the determination of a Km value. Uptake of SDMA by these transporters could be inhibited by known substrates of the respective transport proteins. Furthermore, CAT1 and OATP4C1 also mediate the efflux of SDMA out of cells. These results show that SDMA is a substrate of renally-expressed transport proteins OATP4C1, OCT2, and MATE1 and of CAT1 demonstrating that these transporters are involved in the homeostasis of this uremic toxin and possible sites of interactions with related compounds.